The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/amp0000237
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing the benefits and costs of adaptive cultures for development.

Abstract: Child socialization and development are, in part, products of adapting cultural systems. These systems evolve from the combined influence of collective history and current environmental affordances. They permeate family systems, shaping child development via numerous mechanisms, including structures and roles; values, beliefs, and goals; and parenting-to name a few. Recent growth in the study of child development among racial, ethnic, and cultural minority groups, which has been supported by important cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
138
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(155 citation statements)
references
References 108 publications
16
138
1
Order By: Relevance
“…Finally, neighborhood effects research may benefit from incorporating the fourth major guideline, namely, examining the interplay of biology (Causadias, 2013). Consistent with broad notions about the benefits of socially organized, consonant, and supportive environments for development (Bronfenbrenner & Morris, 2006), alongside models that recognize how adapting cultural systems of socialization work to promote development vis-à-vis opportunities and constraints encoun-tered by bounded groups and communities (White, Nair, et al, 2018), we found substantial evidence that predominantly Latino neighborhoods help to structure Mexican-ori-gin adolescents' community participation and engagement in ways that promote adaptive and mitigate maladaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, neighborhood effects research may benefit from incorporating the fourth major guideline, namely, examining the interplay of biology (Causadias, 2013). Consistent with broad notions about the benefits of socially organized, consonant, and supportive environments for development (Bronfenbrenner & Morris, 2006), alongside models that recognize how adapting cultural systems of socialization work to promote development vis-à-vis opportunities and constraints encoun-tered by bounded groups and communities (White, Nair, et al, 2018), we found substantial evidence that predominantly Latino neighborhoods help to structure Mexican-ori-gin adolescents' community participation and engagement in ways that promote adaptive and mitigate maladaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Dire (helping in emergencies), emotional (helping in emotionally evocative situations), and compliant (helping when asked) prosocial behaviors are especially promoted within Mexican-origin families and communities, particularly those with stronger heritage orientations (Calderón-Tena, Knight, Carlo, Mahrer, & Davis, 2016). Viewed within recent conceptual and theoretical advances (White, Nair, et al, 2018), such findings suggest that systems of socialization within Mexican-origin communities may be especially likely to support the development of these particular types of prosocial behaviors. Thus, though work on neighborhood structural characteristics and prosocial behaviors is limited, especially in the United States, we expected that neighborhood Latino concentration would be associated with higher dire, emotional, and compliant prosocial behaviors.…”
Section: Neighborhood Concentrated Poverty Neighborhood Ethnic-raciamentioning
confidence: 90%
“…The adaptive culture is the result of both culture of origin influences and contextual circumstances and demands; the adaptive culture also has implications for family life, including family interaction patterns, support systems, and routines, and for youth development and adjustment (García Coll et al, 1996). White et al (2018) expanded on the concept of adaptive culture by introducing the notion of "adapting cultural systems" (p. 3) to reflect the idea that cultural systems are transactional and they evolve via continuous interactions between culture of origin influences (i.e., defined by a group's history and cultural traditions, beliefs, and practices) and current contextual circumstances. White et al (2018) proposes that adapting cultural systems are not universally advantageous to youth, but instead may lead to benefits, costs, or both depending on a complex set of factors, such as the particular developmental outcome or competency under consideration, family structures and roles, individual characteristics, contextual demands, and developmental timing.…”
Section: Familism Values Family Relationship Dynamics and Adolescenmentioning
confidence: 99%
“…White et al (2018) expanded on the concept of adaptive culture by introducing the notion of "adapting cultural systems" (p. 3) to reflect the idea that cultural systems are transactional and they evolve via continuous interactions between culture of origin influences (i.e., defined by a group's history and cultural traditions, beliefs, and practices) and current contextual circumstances. White et al (2018) proposes that adapting cultural systems are not universally advantageous to youth, but instead may lead to benefits, costs, or both depending on a complex set of factors, such as the particular developmental outcome or competency under consideration, family structures and roles, individual characteristics, contextual demands, and developmental timing. Applied to the current study, adolescents' familism values were conceptualized as one important feature of their larger adapting cultural systems that were mutually informed by adolescents' culture of origin and their current circumstances.…”
Section: Familism Values Family Relationship Dynamics and Adolescenmentioning
confidence: 99%
See 1 more Smart Citation